Evaluación de los ingresos y gastos de la empresa Expreg S.A del cantón Guayaquil durante el período 2021 - Romero Ojeda, Solange Maribel (2023)
EXPREG S.A. is a private company whose purpose is to offer its customers a variety of motorcycles and original accessories in all brands that lead the Asian market, quality parts at affordable prices. Additionally, this institution offers motorcycle maintenance services. Through this case study we will learn about the financial situation of this institution. Income and expenses are important items that help to analyse and evaluate the economic and financial situation of an entity. In this research, the descriptive method was used in the collection of data and important information, relevant and referring to the problem. Then, the bibliographic method was implemented, which allowed obtaining definitions and concepts for the realization of this case study. In EXPREG S.A. it was evidenced that the results were that the organization's revenues and costs evolve in an ascending way. Expenses increased their post pandemic value, equivalent to the increase in sales commissions in the year 2021.